Bridging the Gap through Investigation of the Impact of Inclusive Education Practices on Student Integration and Academic Outcomes in Vocational High Schools in Jayapura - Jimmi Ari Duri; Halomoan Edy Manurung; Tantry Sitohang Andi Lolo; Magdalena Papuana Biweng (P3KM Politeknik Pertanian Negeri Samarinda, 2025)
This study aims to bridge the gap in the education system in Vocational High Schools (SMK) in Jayapura City by investigating the impact of inclusive education practices on student integration and academic outcomes. Inclusive education, which emphasizes acceptance of student diversity and differences, plays an important role in improving the quality of education and creating a more equitable environment for all students, including those with special needs. This study uses a quantitative approach with a survey method to collect data from students, teachers, and schools regarding the implementation of inclusive education and its impact on students' social integration and academic achievement. The results show that inclusive education practices have a positive influence in improving social integration among students and can contribute to improving students' academic outcomes in SMK in Jayapura City. These findings provide important insights for education policymakers in their efforts to improve the quality and equity of education at the vocational high school level